An improved odor bait for monitoring populations of Aedes aegypti-vectors of dengue and chikungunya viruses in Kenya. Issue 1 (December 2015) - Owino, Eunice; Sang, Rosemary; Sole, Catherine; Pirk, Christian; Mbogo, Charles; Torto, Baldwyn
Abstract Background Effective surveillance and estimation of the biting fraction ofAedes aegypti is critical for accurate determination of the extent of virus transmission during outbreaks and inter-epidemic periods of dengue and chikungunya fever. Here, we describe the development and use of synthetic human odor baits for improved sampling of adultAe. aegypti, in two dengue and chikungunya fevers endemic areas in Kenya; Kilifi and Busia counties. Methods We collected volatiles from the feet and trunks of two female and two male volunteers aged between 25 and 45 years. We used coupled gas chromatography- electroantennographic detection (GC/EAD) analysis to screen for antennally-active components from the volatiles and coupled GC-mass spectrometry (GC/MS) to identify the EAD-active components. Using randomized replicated designs, we compared the efficacies of Biogents (BG) sentinel traps baited with carbon dioxide plus either single or blends of the identified compounds against the BG sentinel trap baited with carbon dioxide plus the BG commercial lure in trappingAe. aegypti . The daily mosquito counts in the different traps were subjected to negative binomial regression following the generalized linear models procedures. Results A total of ten major EAD-active components identified by GC/MS as mainly aldehydes and carboxylic acids, were consistently isolated from the human feet and trunk volatiles from at least two volunteers. Field assays with synthetic chemicals of the shared EAD-active components identified from the feet and trunk gave varying results.Ae. aegypti were more attracted to carbon dioxide baited BG sentinel traps combined with blends of aldehydes than to similar traps combined with blends of carboxylic acids. When we assessed the efficacy of hexanoic acid detected in odors of the BG commercial lure and volunteers plus carbon dioxide, trap captures ofAe. aegypti doubled over the trap baited with the commercial BG lure. However, dispensing aldehydes and carboxylic acids together in blends, reduced trap captures ofAe. aegypti by ~45%-50%. Conclusions Our results provide evidence for roles of carboxylic acids and aldehydes inAe. aegypti host attraction and also show that of the carboxylic acids, hexanoic acid is a more effective lure for the vector than the BG commercial lure.